2021 World Health Organization guideline on pharmacological treatment of hypertension: Policy implications for the region of the Americas - Norm R.C. Campbell; Melanie Paccot Burnens; Paul K. Whelton; Sonia Y. Angell; Marc G. Jaffe; Jennifer Cohn; Alfredo Espinosa Brito; Vilma Irazola; Jeffrey W. Brettler; Edward J. Roccella; Javier Isaac Maldonado Figueredo; Andres Rosende; et al. (Elsevier, 2022)
Summary: Cardiovascular disease (CVD) is the leading cause of death in the Americas and raised blood pressure accounts for over 50% of CVD. In the Americas over a quarter of adult women and four in ten adult men have hypertension and the diagnosis, treatment and control are suboptimal. In 2021, the World Health Organization (WHO) released an updated guideline for the pharmacological treatment of hypertension in adults. This policy paper highlights the facilitating role of the WHO Global HEARTS initiative and the HEARTS in the Americas initiative to catalyze the implementation of this guideline, provides specific policy advice for implementation, and emphasizes that an overarching strategic approach for hypertension control is needed. The authors urge health advocates and policymakers to prioritize the prevention and control of hypertension to improve the health and wellbeing of their populations and to reduce CVD health disparities within and between populations of the Americas.